Implementation of Problem Based Learning Model at Class VII9 of SMP Negeri 21 Pekanbaru - Della Widya Ananda; Kartini Kartini; Nahor Murani Hutapea (Journal of Education and Learning Mathematics Research (JELMaR), 2020)
Abstrack: The proposes of this research are to improve the learning process and to increase mathematics achievement from the students with applied problem based learning model. Class action research is carried out in two cycles. First cycles has three meetings and one daily tests, second cycles has three meetings and one daily tests. The research subject is the students of class VII9 SMP Negeri 21 Pekanbaru in academic year 2019/2020, which total of participants are 39 students, consists of 22 female students and 17 male students with heterogeneous ability. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. The data of the student’s evaluation test showed the number of students who reached KKM on the basic score, daily tests (cycle I), daily tests (cycle II) were 15 people (38,46%), 26 people (66,6%), and 30 people (76,9%). The percentage of KKM achievement shows an increase from before the action to after the action so that it can be said that the learning out comes of students also in crease.The results of this study indicate that the Problem Based Learning model can improve the learning process and improve the mathematics learning out comes of students of VII9 SMP Negeri 21 Pekanbaru in the even semester of the 2019/2020 academic year on material social arithmetic.